Volatile-Mediated Effects Predominate in Paraburkholderia phytofirmans Growth Promotion and Salt Stress Tolerance of Arabidopsis thaliana - Ledger, Thomas; Rojas, Sandy; Timmermann, Tania; Pinedo, Ignacio; Poupin, María J.; Garrido, Tatiana; Richter, Pablo; Tamayo, Javier; Donoso, Raúl (Frontiers in Microbiology, 2016)
Abiotic stress has a growing impact on plant growth and agricultural activity worldwide. Specific plant growth promoting rhizobacteria have been reported to stimulate growth and tolerance to abiotic stress in plants, and molecular mechanisms like phytohormone synthesis and 1-aminocyclopropane-1-carboxylate deamination are usual candidates proposed to mediate these bacterial effects. Paraburkholderia phytofirmans PsJN is able to promote growth of several plant hosts, and improve their tolerance to chilling, drought and salinity. This work investigated bacterial determinants involved in PsJN stimulation of growth and salinity tolerance in Arabidopsis thaliana, showing bacteria enable plants to survive long-term salinity treatment, accumulating less sodium within leaf tissues relative to non-inoculated controls. Inactivation of specific bacterial genes encoding ACC deaminase, auxin catabolism, N-acyl-homoserine-lactone production, and flagellin synthesis showed these functions have little influence on bacterial induction of salinity tolerance. Volatile organic compound emission from strain PsJN was shown to reproduce the effects of direct bacterial inoculation of roots, increasing plant growth rate and tolerance to salinity evaluated both in vitro and in soil. Furthermore, early exposure to VOCs from P. phytofirmans was sufficient to stimulate long-term effects observed in Arabidopsis growth in the presence and absence of salinity. Organic compounds were analyzed in the headspace of PsJN cultures, showing production of 2-undecanone, 7-hexanol, 3-methylbutanol and dimethyldisulfide. Exposure of A. thaliana to different quantities of these molecules showed that they are able to influence growth in a wide range of added amounts. Exposure to a blend of the first three compounds was found to mimic the effects of PsJN on both general growth promotion and salinity tolerance. To our knowledge, this is the first report on volatile compound-mediated induction of plant abiotic stress tolerance by a Paraburkholderia species.